2013
DOI: 10.1002/pd.4090
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maternal weight discrepancies on prenatal screening results for Down syndrome

Abstract: A weight discrepancy of five or more pounds has a significant impact on the risk of Down syndrome; correction of maternal weight would improve the accuracy of the screening test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 7 publications
(9 reference statements)
1
7
0
Order By: Relevance
“…Similar to a previous study that reported maternal weight correction in the first trimester, screening can be best achieved using the log-linear procedure [11]. Although including a weight correction parameter seems to have an almost negligible impact on true positive rates and false positive rates, for an individual woman, weight correction can have a non-negligible impact on calculating specific risk [12]. Thus, to improve the accuracy of screening tests for individual specific risk, the MoM values of serum markers should be adjusted for maternal weight.…”
Section: Discussionmentioning
confidence: 62%
“…Similar to a previous study that reported maternal weight correction in the first trimester, screening can be best achieved using the log-linear procedure [11]. Although including a weight correction parameter seems to have an almost negligible impact on true positive rates and false positive rates, for an individual woman, weight correction can have a non-negligible impact on calculating specific risk [12]. Thus, to improve the accuracy of screening tests for individual specific risk, the MoM values of serum markers should be adjusted for maternal weight.…”
Section: Discussionmentioning
confidence: 62%
“…A recent Canadian study found that, of women with a weight discrepancy of >5 pounds (lbs) (2.3 kg) and within 50 units of the risk cut‐off, the chance of a screening result changing ranged from 33 to 43%. However, among women with a Down syndrome infant, weight discrepancies of up to 15 lbs (~8 kg) made no difference . One possible explanation is that adjustment for weight does not alter screening results when abnormal serum biomarkers levels are pronounced.…”
mentioning
confidence: 99%
“…MoM values provide a simple way to compare the deviation of an individual from the overall population. When using software to calculate Down syndrome risk, the level of serological markers in pregnant women was correlated with their race, age, gestational age, weight, diabetes and smoking, and the correction of gestational age and weight is most significant (21). Several regression equations have been developed for risk estimate correction (6,13,22).…”
Section: Discussionmentioning
confidence: 99%